2008
DOI: 10.1007/s00467-008-0910-2
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia in pediatric community-acquired pneumonia

Abstract: Studies focusing on serum sodium disorders in children with community-acquired-pneumonia (CAP) are nearly entirely lacking, though clinical experience suggests that at least hyponatremia (HN) might be rather common. We evaluated the incidence of hypo- and hypernatremia, in relation to other clinical, laboratory and etiological findings, in pediatric CAP. Serum sodium concentration was measured in 108 ambulatory and hospitalized children with radiologically confirmed CAP of variable severity. The etiology of CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
88
5
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(119 citation statements)
references
References 33 publications
20
88
5
6
Order By: Relevance
“…The proportion of cases with hyponatremia across various diagnostic categories ranged from 3 to 20%. In a recent study by Don M et al, hyponatremia was found in 45.4% of children with community acquired pneumonia [5] incidence of which was similar to present study. 46.5% children with pneumonia had hyponatremia in our study.…”
Section: Discussionsupporting
confidence: 92%
“…The proportion of cases with hyponatremia across various diagnostic categories ranged from 3 to 20%. In a recent study by Don M et al, hyponatremia was found in 45.4% of children with community acquired pneumonia [5] incidence of which was similar to present study. 46.5% children with pneumonia had hyponatremia in our study.…”
Section: Discussionsupporting
confidence: 92%
“…We read with great interest the article entitled "Hyponatremia in pediatric community-acquired pneumonia" by Don et al in the latest issue of this journal [1], and we congratulate their elegant study.…”
Section: Sirsmentioning
confidence: 99%
“…There have been several reports regarding HN in children with pneumonia [1][2][3][4], including the study by Don et al In those studies the authors speculated that the mechanism of HN in pneumonia is due to the syndrome of inappropriate antidiuretic hormone (ADH) secretion and found that HN was associated with the severity in pneumonia. In addition, we here would like to suggest that the deeper the site of inflammation in the respiratory tract, the higher the prevalence of HN in children with RTIs.…”
Section: Sirsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Previous studies have suggested that the presence and degree of hyponatremia is associated with the severity of pneumonia in adults and children, although the results have differed among studies. [3][4][5][6][7] Hyponatremia is caused by various factors, including volume depletion, use of diuretics, hypothyroidism, adrenal insufficiency, heart failure, renal failure, and cirrhosis. Additionally, the syndrome of inappropriate antidiuresis (SIAD) is a frequent and heterogeneous disorder characterized by hyponatremia and impaired urinary dilution in the absence of any recognized stimulation of antidiuretic hormone secretion.…”
mentioning
confidence: 99%